Juvenile amyotrophic lateral sclerosis with complex phenotypes associated with novel SYNE1 mutations. Issue 7 (2nd October 2021) - Naruse, Hiroya; Ishiura, Hiroyuki; Mitsui, Jun; Takahashi, Yuji; Matsukawa, Takashi; Toda, Tatsushi; Tsuji, Shoji
Abstract: Mutations in SYNE1 have been originally described to cause a slowly progressive, pure cerebellar ataxia (spinocerebellar ataxia, autosomal-recessive 8; SCAR8). Notably, recent studies revealed that affected patients with SYNE1 -associated ataxia can present with complex phenotypes rather than pure cerebellar ataxia, including motor neuron and brainstem dysfunctions. We herein report a Japanese patient diagnosed with juvenile amyotrophic lateral sclerosis (ALS) with a complex phenotype, who carried compound heterozygous pathogenic variants in SYNE1 . Of the variants, one was a novel frameshift variant and the other was a nonsense variant previously reported as pathogenic for SCAR8. The patient showed an early age at onset with a relatively slow but progressive course of ALS, accompanied by cognitive decline. Our findings suggest that the clinical spectrum of patients carrying pathogenic SYNE1 variants is broader than expected, and SYNE1 variants should be considered in patients diagnosed with juvenile ALS, even without prominent cerebellar ataxia.